Novel chimeric monoclonal antibodies that block fentanyl effects and alter fentanyl biodistribution in mice - Bhupal Ban; Rodell C. Barrientos; Therese Oertel; Essie Komla; Connor Whalen; Megan Sopko; Yingjian You; Partha Banerjee; Agnieszka Sulima; Arthur E. Jacobson; Kenner C. Rice; Gary R. Matyas; et al. (Taylor & Francis Group, 2021)
The prevalence and societal impact of opioid use disorder (OUD) is an acknowledged public health crisis that is further aggravated by the current pandemic. One of the devastating consequences of OUD is opioid overdose deaths. While multiple medications are now available to treat OUD, given the prevalence and societal burden, additional well-tolerated and effective therapies are still needed. To this point, we have developed chimeric monoclonal antibodies (mAb) that will specifically complex with fentanyl and its analogs in the periphery, thereby preventing them from reaching the central nervous system. Additionally, mAb-based passive immunotherapy offers a high degree of specificity to drugs of abuse and does not interfere with an individual's ability to use any of the medications used to treat OUD. We hypothesized that sequestering fentanyl and its analogs in the periphery will mitigate their negative effects on the brain and peripheral organs. This study is the first report of chimeric mAb against fentanyl and its analogs. We have discovered, engineered the chimeric versions, and identified the selectivity of these antibodies, through in vitro characterization and in vivo animal challenge studies. Two mAb candidates with very high (0.1-1.3 nM) binding affinities to fentanyl and its analogs were found to be effective in engaging fentanyl in the periphery and blocking its effects in challenged animals. Results presented in this work constitute a major contribution in the field of novel therapeutics targeting OUD.